Gastroenterology and Hepatology Training in the Islamic Republic of Iran - Saberifiroozi, M (Iranian Association of Gastroerterology and Hepatology, 2011)
BACKGROUND Training in internal medicine has significantly evolved alongside the development of science, technology and new facilities during the past fifty years. After the specialty of internal medicine, there are multiple subspecialty training programs which have started since 1985 in the Islamic Republic of Iran. In this manuscript we want to define the characteristics of the gastroenterology subspecialty training program in our country. METHODS The characteristics of approved gastroenterology training centers were gathered through a questionnaire. The questionnaire was consisted; the establishment date, the number and academic rank of trainers, the number of trainees, hospital beds, the number and types of diagnostic and therapeutic procedures in a year, the characteristics of training programs and their curriculum composition. The collected data was discussed and revised in a focused group of gastroenterologists from training centers and the board members of Iranian Association of Gastroenterology and Hepatology (IAGH). RESULTS There are 11 training centers with 94 trainers and 65 trainees, with a ratio of trainers to trainees of 1.36. Fifty four percent of trainers are assistant professor. Yearly, 36 new fellows are admitted. Four centers have adequate facilities for training in advanced gastroenterology, and in three centers there are facilities for liver transplantation. The duration of training in internal medicine is four years, whereas in gastroenterology it is two years. The admission for this subspecialty is not university based and with other subspecialty programs, there is a national entrance examination. CONCLUSION There are adequate well known training centers with a suitable ratio of trainer to trainee in the Islamic Republic of Iran. The duration of the GI fellowship is short and implementation of post subspecialty programs for completing the required capabilities of fellows is necessary. The capacity of fellowship admission should be revised according to needs of the country in the fields of health maintenance, research and medical education programs.